Differential responses of chicken monocyte-derived dendritic cells infected with Salmonella Gallinarum and Salmonella Typhimurium - Degpal Singh (Nature Portfolio, 2021)
Abstract Salmonella enterica serovar Gallinarum is a host-restricted bacterial pathogen that causes a serious systemic disease exclusively in birds of all ages. Salmonella enterica serovar Typhimurium is a host-generalist serovar. Dendritic cells (DCs) are key antigen-presenting cells that play an important part in Salmonella host-restriction. We evaluated the differential response of chicken blood monocyte-derived dendritic cells (chMoDCs) exposed to S. Gallinarum or S. Typhimurium. S. Typhimurium was found to be more invasive while S. Gallinarum was more cytotoxic at the early phase of infection and later showed higher resistance against chMoDCs killing. S. Typhimurium promoted relatively higher upregulation of costimulatory and other immune function genes on chMoDCs in comparison to S. Gallinarum during early phase of infection (6 h) as analyzed by real-time PCR. Both Salmonella serovars strongly upregulated the proinflammatory transcripts, however, quantum was relatively narrower with S. Gallinarum. S. Typhimurium-infected chMoDCs promoted relatively higher proliferation of naïve T-cells in comparison to S. Gallinarum as assessed by mixed lymphocyte reaction. Our findings indicated that host restriction of S. Gallinarum to chicken is linked with its profound ability to interfere the DCs function. Present findings provide a valuable roadmap for future work aimed at improved vaccine strategies against this pathogen.